2015
DOI: 10.3390/v7052592
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Tumor Viruses with Host Cell Surface Receptors and Cell Entry

Abstract: Currently, seven viruses, namely Epstein-Barr virus (EBV), Kaposi’s sarcoma-associated herpes virus (KSHV), high-risk human papillomaviruses (HPVs), Merkel cell polyomavirus (MCPyV), hepatitis B virus (HBV), hepatitis C virus (HCV) and human T cell lymphotropic virus type 1 (HTLV-1), have been described to be consistently associated with different types of human cancer. These oncogenic viruses belong to distinct viral families, display diverse cell tropism and cause different malignancies. A key to their patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 206 publications
(250 reference statements)
1
50
0
Order By: Relevance
“…Virions bind initially to heparan sulfate proteoglycans (HSPGs), which serve as primary attachment receptors on basal cells or exposed basement membrane resulting from epithelial trauma or permeabilization [39]. Initial L1 attachment to HSPGs induces conformational changes in the virus capsid ultimately resulting in loss of affinity for the primary receptor and transfer of the virus to an as of yet poorly characterized entry receptor.…”
Section: 5 Hpv Productive Infection and Lifecyclementioning
confidence: 99%
“…Virions bind initially to heparan sulfate proteoglycans (HSPGs), which serve as primary attachment receptors on basal cells or exposed basement membrane resulting from epithelial trauma or permeabilization [39]. Initial L1 attachment to HSPGs induces conformational changes in the virus capsid ultimately resulting in loss of affinity for the primary receptor and transfer of the virus to an as of yet poorly characterized entry receptor.…”
Section: 5 Hpv Productive Infection and Lifecyclementioning
confidence: 99%
“…Another interesting study describes a role for CIB1 in the regulation of macropinocytosis and cellular entry of Kaposi's sarcoma-associated herpes virus (KSHV; also k n o w na sh u m a nh e r p e sv i r u s8 )( 6 4 ) .K S H Vh a sb e e n linked to several cancers, including Kaposi'ss a r c o m a , primary effusion lymphoma, and multicentric Castleman's disease. To gain entry into host cells, KSHV binds to several cell-surface receptors, including aVintegrinsandtyrosine kinase receptor family member EphA2, which results in activation of intracellular signaling events that promote macropinocytosis and internalization of the virus (78). Of interest, the researchers found that CIB1 directly interacts with EphA2 and that CIB1 depletion significantly reduces KSHV entry and infection of endothelial cells (64).…”
Section: Cib1 and Cancermentioning
confidence: 99%
“…The molecular mechanism of hepatitis C virus (HCV) entry has been revealed by genomic and proteomic technologies. (1) First, HCV infection is mediated by HCV complexing with lipoproteins, which interact with heparan sulphate proteoglycans (HSPGs) on the surface of hepatocytes. Following attachment to HSPGs, in the second phase of infection, HCV associates with several specific entry coreceptors, such as CD81, scavenger receptor class B type 1 (SRB1) and claudin 1 (CLDN-1), to prepare the virus for hepatocyte entry.…”
mentioning
confidence: 99%